2006
DOI: 10.1111/j.1525-1497.2006.00591.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with medication refill adherence in cardiovascular-related diseases

Abstract: BACKGROUND: The factors influencing medication adherence have not been fully elucidated. Inadequate health literacy skills may impair comprehension of medical care instructions, and thereby reduce medication adherence. OBJECTIVES: To examine the relationship between health literacy and medication refill adherence among Medicare managed care enrollees with cardiovascular‐related conditions. RESEARCH DESIGN: Prospective cohort study. SUBJECTS: New Medicare enrollees from 4 managed care plans who completed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
232
3
12

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 323 publications
(260 citation statements)
references
References 56 publications
13
232
3
12
Order By: Relevance
“…13 Non-respondents were slightly older with higher educational attainment and were more likely to be white and living in zip codes with higher median income 10 . Additional details of this survey have been published previously 6,10,[14][15][16][17][18] . Starting with this sample of 3,260, we excluded 282 subjects with history of stroke, 55 with severe cognitive impairment (MiniMental State Examination Score<18), and 99 with a missing value in one of the fields examined in this study 18,19 , leaving a final analytic sample of 2,824.…”
Section: Methodsmentioning
confidence: 99%
“…13 Non-respondents were slightly older with higher educational attainment and were more likely to be white and living in zip codes with higher median income 10 . Additional details of this survey have been published previously 6,10,[14][15][16][17][18] . Starting with this sample of 3,260, we excluded 282 subjects with history of stroke, 55 with severe cognitive impairment (MiniMental State Examination Score<18), and 99 with a missing value in one of the fields examined in this study 18,19 , leaving a final analytic sample of 2,824.…”
Section: Methodsmentioning
confidence: 99%
“…One study that has done so did not explore differences by patient race. 44 The complex mix of patient, physician, and system factors associated with both medication adherence [45][46][47] and treatment intensification 42,[48][49][50] has been well documented, as have the ongoing challenges in achieving clinical control even when patients are adherent and treatment is intensified. 44,51,52 It is therefore encouraging to see that within a relatively short follow-up period, a substantial percentage of patients who were in poor control at baseline were able to achieve recommended control levels.…”
Section: Discussionmentioning
confidence: 99%
“…In the managed care setting, evidence indicates that education for patients can improve statin treatment adherence and, in turn, increased medication adherence is associated with a greater likelihood of achieving LDL-C goals. 8,9 Parris et al showed that medication adherence did not significantly differ among patients receiving atorvastatin, pravastatin, or simvastatin, and no significant differences were seen in mean LDL-C levels. 9 However, LDL-C goal attainment is of substantial concern in managed care and has been shown to be suboptimal, especially in high-risk patients.…”
Section: Introductionmentioning
confidence: 99%